Q. 233.8( 4 Votes )

If x + y + z = 0,

Answer :

Given: x + y + z = 0

To Prove:


Taking LHS,


Expanding along the first row, we get


= xa{(za)(ya) – (xc)(xb)} – (yb){(yc)(ya) – (zb)(xb)} + (zc){(yc)(xc) – (zb)(za)}


= xa{a2yz – x2bc} – yb{y2ac – b2xz} + zc{c2xy – z2ab}


= a3xyz – x3abc – y3abc + b3xyz + c3xyz – z3abc


= xyz(a3 + b3 + c3) – abc(x3 + y3 + z3)


It is given that x + y + z = 0


x3 + y3 + z3 = 3xyz


= xyz(a3 + b3 + c3) – abc (3xyz)


= xyz(a3 + b3 + c3 – 3abc)



Hence Proved


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Three schools A, Mathematics - Board Papers

Using properties Mathematics - Board Papers

Two schools A andMathematics - Board Papers

State True or FalMathematics - Exemplar